Association between Psychological Stress and Periodontitis: A Systematic Review - Castro, Micaele M. L.; Ferreira, Railson de O.; Fagundes, Nathalia C. F.; Almeida, Anna P. C. P. S. C.; Maia, Lucianne C.; Lima, Rafael R. (European Journal of Dentistry, 2020)
This systematic review aims to investigate the association between psychological stress and periodontitis through analysis of cortisol levels and periodontal clinical parameters. This review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guide and based on PECO (Participants, Exposure, Comparators, Outcomes) question and registered at PROSPERO under the code CRD42017076670. As eligibility criteria, observational studies performed in adult humans presenting periodontitis (P), which evaluated patients exposed (E) and nonexposed to psychological stress (C) and to verify the association between this type of stress and periodontitis (O) were included. The searches were performed until March 2018. The following databases were used: PubMed, Scopus, Web of Science, The Cochrane Library, LILACS, OpenGrey, and Google Scholar. After searches, the duplicate results were removed. The remaining citations were selected according to eligibility criteria in two phases. In the first phase, the title/abstract was evaluated. In the second phase, the articles were chosen previously were assessed by full text. After selection, the studies were submitted to data extraction and risk of bias evaluation by Fowkes and Fulton. A total of 1,386 citations were retrieved. After duplicates removal and selection process, three articles were selected by full text. Among them, two articles reported a positive association between psychological stress and periodontitis. All articles were classified as low risk of bias. Even though two articles highlighted an association between psychological stress and the presence of a possible modulatory pattern of cortisol levels in clinical parameters of periodontitis, more studies are necessary to elucidate this question.
Keywords: stress; psychological; periodontitis; periodontal disease; systematic review